Playing with Modernity: The Decolonization of Indian Cricket (Altre Modernità, 2015)
For the former colony, decolonization is a dialogue with the colonial past, and not asimple dismantling of colonial habits and modes of life. Nowhere are the complexitiesand ambiguities of this dialogue more evident than in the vicissitudes of cricket inthose countries that were once part of the British Empire. In the Indian case, thecultural aspects of decolonization deeply affect every domain of public life, fromlanguage and the arts to ideas about political representation and economic justice. lnevery major public debate in contemporary India, one underlying strand is always thequestion of what to do with the shreds and patches of the Colonial heritage. Some ofthese patches are institutional; others are ideological and aesthetic.